2019
DOI: 10.18632/oncotarget.24684
|View full text |Cite
|
Sign up to set email alerts
|

Roles of GLUT-1 and HK-II expression in the biological behavior of head and neck cancer

Abstract: The Warburg effect plays an important role in the proliferation and invasion of malignant tumors. Glucose transporter 1 and hexokinase II are two key energy transporters involved in mediating the Warburg effect. This review will analyze the mechanisms of these two markers in their effects on the biological behavior of head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 137 publications
1
36
0
Order By: Relevance
“…Numerous studies have shown that GLUT-1 overexpression in tumours from different sites can suggest a worse prognosis, such as in colorectal cancer [ 9 ], lung cancer [ 10 ], mesothelioma [ 11 ], head and neck carcinoma [ 12 ], ovarian cancer [ 13 ], urothelial carcinoma [ 14 ], prostate cancer [ 15 ], esophagogastric cancer [ 16 , 17 ] and sarcomas [ 18 ]. The existing data on the prognostic significance of the overexpression of GLUT-1 in pancreatic ductal adenocarcinoma (PDAC) has been limited and not consistent, having increased exponentially in recent years with positive results.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that GLUT-1 overexpression in tumours from different sites can suggest a worse prognosis, such as in colorectal cancer [ 9 ], lung cancer [ 10 ], mesothelioma [ 11 ], head and neck carcinoma [ 12 ], ovarian cancer [ 13 ], urothelial carcinoma [ 14 ], prostate cancer [ 15 ], esophagogastric cancer [ 16 , 17 ] and sarcomas [ 18 ]. The existing data on the prognostic significance of the overexpression of GLUT-1 in pancreatic ductal adenocarcinoma (PDAC) has been limited and not consistent, having increased exponentially in recent years with positive results.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that cancer cells show more rapid glucose uptake and metabolism, i.e. increased expression of glucose transporter 1 (GLUT-1) and HK-II, than normal cells; these characteristics enable rapid growth and division [50]. Hyperglycemia and hyperlipidemia are the main pathologic features of the metabolic disorders that comprise DM, and hyperglycemia implies the availability of an of the most important metabolic substrate for tumor cells [51].…”
Section: Hyperglycemiamentioning
confidence: 99%
“…Mice in the Ab+ Bi+ RT group showed the highest expression of TNF-α, suggesting that Ab+ Bi+ RT plays a significant role in tumor cell apoptosis. Glut-1 is the major glucose transporter in tumor cells that provides glucose for energy production [43] . Accordingly, Glut-1 expression closely correlates with tumor invasiveness and poor prognosis.…”
Section: Dsbsmentioning
confidence: 99%